The Influence between Debt to Asset Ratioand Debt to Equity Ratio towards the Profit Quality Based on Du Pont Analysis - harjanti, wulandari (Archives of Business Research, 2019)
This study aims to examine the influence between debt to asset ratio and debt to equity ratio towards the quality of Du Pont Analysis-based company profit. This study usedquantitative approach, where the selected samples were the company stocks belong to the index of LQ45 in IndonesiaStock Exchange in 2017. By using multiple linear regression, the conclusion of this article found that debt to equity ratio and debt to asset ratio simultaneously gave positive influence towards the quality of profit. Meanwhile, the debt to equity partially gave negative influence towards the quality of profit, whereas the debt to asset ratio positively influenced it too.